ANALISIS SUMBER BELAJAR DALAM PEMBELAJARAN IPA DI SDI NURUL HIDAYAH - rendi, Rendi (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2025)
This study aims to analyze learning resources in science education at SDI Nurul Hidayah. The research uses a qualitative approach with data collection techniques in the form of in-depth interviews and direct observations. The results show that teachers at SDI Nurul Hidayah utilize various types of learning resources, including place-based learning resources, material-based learning resources, people-based learning resources, book-based learning resources, and event-based learning resources. Based on the observations, each type of learning resource has its own advantages and challenges. For instance, place-based learning resources such as the school yard and garden are often limited by weather conditions, time constraints, and insufficient logistics. Material-based learning resources, such as teaching aids, models, and natural objects, face limitations in terms of quantity and availability. The findings indicate that in order to achieve the optimal learning outcomes in science education, teachers need to manage the learning process effectively and engagingly. Therefore, it can be concluded that proper science education supports the teaching and learning process in elementary schools, although optimizing resources, increasing the number and availability of teaching aids, and improving teachers' skills are areas that still require enhancement